ANALYSIS OF ETHANOL FORMATION WITH THE ADDITION OF FE2O3, NIO,, AND CUO OXIDES FROME ARTCIFIAL PAL OIL MILL EFFLUENT (POME) IN ANAEROBIC PROCESSES - Salahudin Rabbani, Muammar
Indonesia is the world's largest palm oil producer with a production of 45.5 million metric tons in 2022. Large palm oil production certainly produces waste from the processing of oil palm fruit into CPO or what is commonly called Palm Oil Mill Effluent (POME). Processing of liquid waste produced from CPO production can produce renewable energy with one of its products being bioethanol. In the anaerobic POME processing process, the addition of trace elements such as Al (aluminum) Cu (copper), Ni (nickel), Fe (iron), and others will affect the formation of ethanol. The metals used in this study are metal oxides such as Fe (iron), Cu (copper), and Ni (nickel). The anaerobic process is carried out using a Circulated Batch Reactor (CBR) reactor. Stirring using nitrogen is required to create an anaerobic atmosphere before the reactor is operated. Sampling of the reactor is carried out every 6 hours for pH, VSS, DO parameters. The DO results obtained were that the acidogenesis process lasted an average of 18 hours, which was marked by a decrease in pH to reach a range of 4.5-5.0. Bacterial growth experienced in each variation of the experiment showed a positive trend with an increase in VSS. The effect of adding metal oxides did not produce a positive value, but when compared to the reactor without adding metal, the reactor with the addition of CuO metal, a combination of Fe2O3 and CuO, and a combination of a mixture of 3 metals produced a degree of ethanofication (DE) greater than the reactor without adding metal. Consecutively, the average values of replication 1 and 2 degree of ethanofication from the 3 reactors were -0.221; -0.153; -0.221. Furthermore, the direction of the formation of the reactor with the addition of NiO metal oxide will produce better volatile acid products than without adding NiO. However, the mass balance results prove that there are still around 50-60% other forms produced from COD degradation other than ethanol and TAV tested in this study.